Effectiveness of Acupuncture for Early Recovery of Bowel Function in Cancer: A Systematic Review and Meta-Analysis. (20th December 2017) - Liu, Yi-Hua; Dong, Guang-Tong; Ye, Yang; Zheng, Jia-Bin; Zhang, Ying; Lin, Hong-Sheng; Wang, Xue-Qian
Abstract : Objectives . The aim of this study was to evaluate the effects of acupuncture therapy to reduce the duration of postoperative ileus (POI) and to enhance bowel function in cancer patients. Methods . A systematic search of electronic databases for studies published from inception until January 2017 was carried out from six databases. Randomized controlled trials (RCTs) involving the use of acupuncture and acupressure for POI and bowel function in cancer patients were identified. Outcomes were extracted from each study and pooled to determine the risk ratio and standardized mean difference. Results . 10 RCTs involving 776 cancer patients were included. Compared with control groups (no acupuncture, sham acupuncture, and other active therapies), acupuncture was associated with shorter time to first flatus and time to first defecation. A subgroup analysis revealed that manual acupuncture was more effective on the time to first flatus and the time to first defecation; electroacupuncture was better in reducing the length of hospital stay. Compared with control groups (sham or no acupressure), acupressure was associated with shorter time to first flatus. However, GRADE approach indicated a low quality of evidence. Conclusions . Acupuncture and acupressure showed large effect size with significantly poor or inferior quality of included trials for enhancing bowel function in cancer patients after surgery. Further well-powered evidence is needed.